2006
DOI: 10.1111/j.1439-0507.2006.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of panomycocin, a novel exo‐β‐1,3‐glucanase isolated from Pichia anomala NCYC 434, against dermatophytes

Abstract: Killer proteins that are produced and secreted into the environment by certain yeast strains are considered as promising antifungal agents. In this study, in vitro activity of Pichia anomala NCYC 434 (K5) killer protein, panomycocin, which is a 49 kDa glycoprotein with an exo-beta-1,3-glucanase activity was tested against 41 isolates of dermatophytes. Minimum inhibitory concentrations (MICs) were determined by a broth microdilution method based on the reference document M38-A of Clinical and Laboratory Standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
1
17
0
2
Order By: Relevance
“…Polonelli et al (1990) were the first to show that P. anomala killer toxin was active in vivo in experimental mice. More recently, Izgü et al (2006) have shown that the K5 killer toxin of P. anomala displays activity against selected dermatophytes (Microsporum spp. and Trichophyton spp).…”
Section: P Anomala In Industrymentioning
confidence: 99%
“…Polonelli et al (1990) were the first to show that P. anomala killer toxin was active in vivo in experimental mice. More recently, Izgü et al (2006) have shown that the K5 killer toxin of P. anomala displays activity against selected dermatophytes (Microsporum spp. and Trichophyton spp).…”
Section: P Anomala In Industrymentioning
confidence: 99%
“…was reported to be prohibited by endo-β-1,3-glucanases from Pichia anomala and Paenibacillus sp. (8). C. albicans is a dimorphic fungus that can switch from a unicellular yeast form to one characterized by mycelial hyphae, thereby enhancing its virulence as a fungal pathogen.…”
mentioning
confidence: 99%
“…Killer toxins from the genus Pichia have heterogeneous mechanisms of activity; some of them have similar characteristics to that determined for the P. membranifaciens PMKT (Santos & Marquina, 2004a;Pfeiffer & Radler, 1984;Middelbeek et al, 1979), and others do not. PaT, the killer toxin produced by P. acaciae, has a tRNase activity (Klassen et al, 2008) whereas P. anomala NCYC 434 has an exo-b-1,3-glucanase activity against sensitive yeast strains (Izgü et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Strains of Pichia membranifaciens are common contaminants in food-related environments and occur with high frequency in fermenting olive brines (Marquina et al, 1992(Marquina et al, , 1997. Within the genus Pichia, which is heterogeneous from a taxonomic point of view (Kurtzman & Fell, 1998;Kurtzman & Robnett, 1998), P. acaciae (McCracken et al, 1994;Klassen et al, 2008), P. anomala (Comitini et al, 2004;Wang, et al, 2007;Izgü et al, 2007), P. farinosa (Suzuki & Nikkuni, 1994), P. inositovora (Klassen & Meinhardt, 2003) and P. kluyveri (Middelbeek et al, 1979) produce different killer toxins. Killer toxins from the genus Pichia have heterogeneous mechanisms of activity; some of them have similar characteristics to that determined for the P. membranifaciens PMKT (Santos & Marquina, 2004a;Pfeiffer & Radler, 1984;Middelbeek et al, 1979), and others do not.…”
mentioning
confidence: 99%